2008
DOI: 10.2500/ajr.2008.22.3221
|View full text |Cite
|
Sign up to set email alerts
|

Does Nasal Irrigation Enter Paranasal Sinuses in Chronic Rhinosinusitis?

Abstract: Nasal douche and spray is not effective in delivering a nasal irrigation solution into paranasal sinuses in chronic rhinosinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 19 publications
0
72
0
Order By: Relevance
“…A relatively low dose of active drug is probably delivered to the mucosa using irrigation systems although the exact exposure is undetermined at present. 775,806,808 This may not be the case with small-volume, high-dose nebulized devices for which no safety data is as yet available. Longer-term adequately powered RCTs are needed on these safety issues.…”
Section: Viiie1 Crswnp Management:-saline (Spray and Irrigation)mentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively low dose of active drug is probably delivered to the mucosa using irrigation systems although the exact exposure is undetermined at present. 775,806,808 This may not be the case with small-volume, high-dose nebulized devices for which no safety data is as yet available. Longer-term adequately powered RCTs are needed on these safety issues.…”
Section: Viiie1 Crswnp Management:-saline (Spray and Irrigation)mentioning
confidence: 99%
“…Studies have shown that ESS increases the penetration of topical irrigation therapy from minimal absorption (<2%) to greater than 95% absorption. 717,774,775 Four RCTs and 6 systematic reviews have examined topical antibiotics in CRS (Table VII-18).…”
Section: Viie4 Crssnp Management: Antibioticsmentioning
confidence: 99%
“…[4][5][6] The edematous inflammatory mucosa and ostiomeatal occlusion often seen in CRS allows Ͻ1% of solution volume to enter the sinus cavities before surgery. 7 The extent of sinus surgery varies across institutions. This difference brings about variable access and sinus penetration.…”
mentioning
confidence: 99%
“…In studies similar to this pilot study, the amount of radiographic contrast used varied between 0.3 ml and 40 ml (drops, 1.5 ml per naris; 9 spray, 0.3-10 ml per naris; 5,8,9 syringe, 40 ml per naris; 5,8 and sinus wash, 20 ml per naris). 4 The smaller end of the spectrum was probably selected to reflect typical volumes used in nasal medications, whereas the larger amounts (i.e.…”
Section: 13mentioning
confidence: 99%
“…3 Contrast agents are employed by many imaging modalities and can easily improve signal-to-noise ratio by improving tissue contrast. Several studies used contrast agents, namely iodine, in the nasal and paranasal sinuses to assess nasal/sinus drug delivery using MDCT, 4,5 nuclear medicine [6][7][8] and CBCT. 9 To our knowledge, topical application of contrast agents in the upper airway as a method to enhance tissue contrast has not been investigated.…”
Section: Introductionmentioning
confidence: 99%